2021
DOI: 10.3389/fgene.2021.687745
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Risk of Common Autoimmune Inflammatory Diseases—Evidence From a Large-Scale Genetic Analysis Totaling 1 Million Individuals

Abstract: Purpose: Observational studies have suggested a protective effect of alcohol intake with autoimmune disorders, which was not supported by Mendelian randomization (MR) analyses that used only a few (<20) instrumental variables.Methods: We systemically interrogated a putative causal relationship between alcohol consumption and four common autoimmune disorders, using summary-level data from the largest genome-wide association study (GWAS) conducted on inflammatory bowel disease (IBD), rheumatoid arthritis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Leveraging 2-sample mendelian randomization (MR), several studies reported directional effects for pairs of psychiatric and immune-related phenotypes, including positive effects of schizophrenia on systemic lupus erythematosus and immune-mediated bowel and biliary diseases and positive effects of major depression and alcohol use on asthma . On the other hand, several MR studies found nonsignificant effects pertaining to certain psychiatric-immune comorbidities . Another possibility is that shared liability is influenced by a correlated third variable with associations with one or both phenotypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leveraging 2-sample mendelian randomization (MR), several studies reported directional effects for pairs of psychiatric and immune-related phenotypes, including positive effects of schizophrenia on systemic lupus erythematosus and immune-mediated bowel and biliary diseases and positive effects of major depression and alcohol use on asthma . On the other hand, several MR studies found nonsignificant effects pertaining to certain psychiatric-immune comorbidities . Another possibility is that shared liability is influenced by a correlated third variable with associations with one or both phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 On the other hand, several MR studies found nonsignificant effects pertaining to certain psychiatric-immune comorbidities. [18][19][20][21] Another possibility is that shared liability is influenced by a correlated third variable with associations with one or both phenotypes. Many risk factors are associated with both psychiatric and immune-related disorders, briefly reviewed within the eMethods of Supplement 1.…”
mentioning
confidence: 99%
“…A number of environmental factors associated with MS development have been discovered through large case-control and cohort studies, including infectious mononucleosis, obesity during adolescence, cigarette smoking, and low serum vitamin D 2 . A protective link between alcohol consumption and MS risk has been demonstrated in Swedish 3,4 and Danish 5 cohorts, but evidence from other cohorts 6 and mendelian randomisation studies 7,8 have failed to support this relationship.…”
mentioning
confidence: 99%
“…Several studies have demonstrated that alcohol modulates the immune system in a dose- and time-dependent manner ( 40 , 41 ). However, in a recent Mendelian randomization analysis conducted by Xia Jiang et al., alcohol intake did not show a causal role in IBD risk ( 42 ). In addition, our study did not find any association between alcohol intake and IBD either.…”
Section: Discussionmentioning
confidence: 99%